Learning: Design, Engagement and Definition Interdisciplinarity and learning - Hokanson, Brad.; Exter, Marisa; Grincewicz, Amy.; Schmidt, Matthew; Tawfik, Andrew A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This book examines the topic of learning design from a human, interactive, and collaborative perspective. A variety of pedagogic and instructional modalities are thoroughly investigated as methodologies for creating functional and effective designs for students. The book is appropriate for all levels of teaching and learning, but special attention is paid to the special requirement of higher education, graduate education and post-graduate classrooms. Within the research chapters are embedded numerous examples, case studies, and implementation guides. The book is a scholarly yet practical guide to learning design and everyone from educational researchers in all areas of educational technology to instructional designers and instructional technologists will find it useful and inspiring at once. .
Introduction -- A Framework for Inquiry on Instructed Learning -- Making Decisions about Asynchronous and Synchronous Engagement Strategies: Access and Inclusion -- Using Live Interactive Improv to Instill a Participatory, Transactional Learning Culture in the Classroom -- Instructional Design as a Way of Acting in Relationship with Learners -- The Case for Rethinking Multimedia -- Designing Master Courses that Promote Significant, Engaged Learning -- Analogies, Metaphors, and Similes as We Ponder Anew the Aims, Design, and Meaning of Learning -- Learning experience in an Instructional Design doctoral program: A re-design case -- Current and Emerging Views of Learner Experience from the Field of Learning Design & Technology -- Learning to learn lifelong across domains and disciplines: Heutagogy and movement towards triple-loop learning -- Social Media for Connected Learning and Engagement in Online Education -- Design of Learning Experience to Engage Learning in an Instructional Design and Technology Graduate-Level Class: DGBL (Digital-Game-Based-Learning) Cases -- Using Psychological Theories to Enhance Guided Inquiry Design -- The Nature of Learning in Highly Collaborative Environments -- Digital Interactives To Improve Learning In Haiti - Research Innovation And Scholarly Excellence (RISE) Grant Project -- Human Systems Dynamics in Interdisciplinary Education: A Complexity Theory Approach -- A Case Study of China$1 (Bs Edtech Response to the Coronavirus Outbreak: Examining Learning Experiences Designs with a Multidimensional Learning Framework -- Design and Development of Mobile Simulation for Preservice Teacher$1 (Bs Classroom Management Skill Training -- (3z(BTell me about this shoe(3y(B: object-based learning experiences for undergraduates -- Transforming Universities Into Learning Organizations -- Strategies for Creating Engaging Learning Communities to Inspire & Motivate Adult Learners -- The Invisible Message -- Blocks, Access, Success and Engagement: Learning Design Considerations in Progress-Monitoring Tools for American Sign Language or English -- Neurotechnologies and the Neurodiversity Movement for Defining Learners, Designing Multimedia Learning Spaces, and Evaluating Learning -- Strategies for Creating Engaging Learning Communities to Inspire & Motivate Adult Learners.s
Keywords: Educational technology; Education, Higher; Digital Education and Educational Technology; Higher Education